2017
DOI: 10.1016/j.drugalcdep.2017.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco demand, delay discounting, and smoking topography among smokers with and without psychopathology

Abstract: Introduction Tobacco demand (i.e., relative value attributed to a given reinforcer) and delay discounting (i.e., relative preference for smaller immediate rewards over larger delayed rewards) are two behavioral economic processes that are linked to the progression of problematic substance use. These processes have not been studied among those with psychopathology, a vulnerable group of smokers. The current study examined differences in tobacco demand and delay discounting, and their association with smoking to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The average pack price in the United States is approximately $7 making average single cigarette costs $0.35. Some P max estimates for cigarettes from purchase task studies have exceeded this value consistent with the results observed here (e.g., P max greater than $1 USD [or equivalent] for full nicotine or typical brand cigarettes; Farris, Aston, Abrantes, & Zvolensky, ; Higgins et al, ; MacKillop et al, ). One of the few studies to report a P max ($0.25) more closely approximating market price used a high‐resolution evaluation and included the price/pack next to each price/cigarette (MacKillop et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…The average pack price in the United States is approximately $7 making average single cigarette costs $0.35. Some P max estimates for cigarettes from purchase task studies have exceeded this value consistent with the results observed here (e.g., P max greater than $1 USD [or equivalent] for full nicotine or typical brand cigarettes; Farris, Aston, Abrantes, & Zvolensky, ; Higgins et al, ; MacKillop et al, ). One of the few studies to report a P max ($0.25) more closely approximating market price used a high‐resolution evaluation and included the price/pack next to each price/cigarette (MacKillop et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Since 2000, Chen et al published a study wherein a total puffing volume of 360 mL/cigarette was determined [22], i.e., the lowest value we could identify. This is almost four times lower than the 1289 mL/cigarette calculated with the data from Ross et al and Farris et al [23,24], i.e., the highest total puffing volume reported. The variation in puffing topography data published thus far may be explained by differences between cigarette brands as well as by inter-individual and intra-individual differences.…”
Section: Introductionmentioning
confidence: 50%
“…As we mentioned above, such variations may be a function of sex, nicotine yield, cigarette type (flavored vs. none flavored) ethnicity, etc. [ 9 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%